RESPONS PEMBERIAN PUPUK ORGANIK CAIR DAN NPK PADA TANAMAN BIWA ( Eriobotrya japonica Lindl. ) DI MAIN NURSERY - Mery Susana Tarigan; Asil Barus; Fatiani Manik (Jurnal Agroekoteknologi, 2015)
ABSTRACTResponse of Giving Liquid Organic Fertilizer and NPK At Biwa Plant (Eriobotrya japonica Lindl.) Inthe Main Nursery. Biwa plant nurseries face constraints in fertilizer recommendation. Thereforethrough liquid organic fertilizer and NPK plant is expected to boost growth in the nursery biwa.Research conducted at the Experiment Berastagi in March - June, 2013, using a factorial randomizedblock design with two factors: the concentration of organic manure (0, 5, 10 ml / L) and NPK fertilizerdoses (0, 5, 10 and 15 g / polybag ). The parameters measured were plant height, stem diameter, crownwidth, of the number of leaves, number of leaf chlorophyle and total leaf area. The results showed thatthe liquid fertilizer oganik significant effect on the amount of leaf chlorophyll but not significant effecton other parameters. NPK fertilizer significant effect on plant height, stem diameter, crown width, of thenumber of leaves, and total leaf area. Their interaction effect was not significant on all variablesobservations. The best results from this study were obtained in the treatment of liquid organic fertilizer10ml / L and 5 g of NPK fertilizer / polybag.Keywords: nursery, organic liquid fertilizer, NPK fertilizer, biwa.